A photodiode based on PbS nanocrystallites for FYTRONIX solar panel automatic tracking controller - Wageh, S.; Farooq, W. A.; Tataroglu, A.; Dere, A.; Al-Sehemi, Abdullah G.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier, 2017)
The structural, optical and photoelectrical properties of the fabricated Al/PbS/p-Si/Al photodiode based on PbS nanocrystallites were investigated. The PbS nanocrystallites were characterized by X-ray diffraction (XRD), UV-VIS-NIR, Infrared and Raman spectroscopy. The XRD diffraction peaks show that the prepared PbS nanostructure is in high crystalline state. Various electrical parameters of the prepared photodiode were analyzed from the electrical characteristics based on I-V and C-V-G. The photodiode has a high rectification ratio of 5.85x10(4) at dark and +/- 4 V. Moreover, The photocurrent results indicate a strong photovoltaic behavior. The frequency dependence of capacitance and conductance characteristics was attributed to depletion region behavior of the photodiode. The diode was used to control solar panel power automatic tracking controller in dual axis. The fabricated photodiode works as a photosensor to control Solar tracking systems.
Keywords: PbS nanocrystallite; Photodiode; Photoconduction; Transient measurements